(untitled) (Physical Education, Health and Social Sciences, 2025)
Malaria is a major cause of anemia in children with a complex, bidirectional relationship caused by the parasite plasmodium leading to hemolysis and anemia. The aim of this study to investigate the prevalence of malaria with anemia in children admitted at Khairpur Medical College Civil Hospital District Khairpur. Methodology: Study was conducted on 260 patients of malaria with anemia, and 150 individuals were used as control group. Demographic result showed socioeconomics, residential locations, literacy and detailed history about malaria and anemia. The finding from survey questionnaire, we concluded that socioeconomic conditions, residential locations and literacy rate are significant risk factors of the disease. Result: The incidence of correlation of malaria with anemia is determined to be higher in male than female children with school going child above the 5 years of age. The study population consisted of 55% males and 45% females. There were 150 control patients and/160 case patients (infected youngsters). According to demographic data, 24% of children lived in urban areas and 76% of children lived in rural areas. Socioeconomic status of anemia with malaria children`s guardians were categorized into three different classes on the bases of their monthly income, Upper class 0% middle class 15%, lower class 85%. The literacy status of parents/ guardians showed that 8% parents were literate whereas 92% parents were illiterate. Significant majority (92%) of guardians were unaware of anemia. 58% children reported experiencing malaria more than twice. The 208 children were plasmodium vivax positive, 42 children were plasmodium falciparum positive, and 10 patients have mixed picture. Conclusion: This study emphasizes the prevalence of malaria with anemia play a very important role in population of Kahirpur Pakistan. Demographic findings revealed that boys were more affected with malaria than girls, 36% were preschool age children were affected with malaria 14% were infants, Majority of study population were belonged to the lower class, due to the lack of education majority of parents were showed no any knowledge about sever anemic condition of their children, 80% Plasmodium vivax positive patients whereas 16% of plasmodium falciparum positive patients.